Analysis on Entrepreneurship Psychology of Preschool Education Students With Entrepreneurial Intention - Yin, Yiwei; Yang, Liu; Liu, Bojing (Frontiers in Psychology, 2020)
To diversify the creative thinking of preschool education students and improve their ability to innovate and start a business, a survey of preschool education students under entrepreneurial psychology theory is conducted. Based on the theoretical foundation of entrepreneurial psychology, this paper analyzes the entrepreneurial psychological quality and psychological education of college students. By investigating preschool education students in a certain college in Sichuan as the research subject, this paper explores the current entrepreneurial intentions of college students and their entrepreneurial psychological problems. Aiming at the current entrepreneurial situation of college graduates, from the perspective of the school, relevant countermeasures are proposed to support college students' entrepreneurial psychology. Among the 205 preschool education college students, the students are more willing to give full play to their professional expertise in terms of employment intentions. At the same time, there are still situations in which students are not satisfied with the prospects of preschool education career development and want to achieve the value of life through other methods. Most students in preschool education have a wait-and-see attitude toward entrepreneurship. Only 35% of students have a clear intention to start a business and have their plans for entrepreneurship. More than 90% of students believe that their entrepreneurial ability is weak, and 80% of students believe that their professional knowledge is lacking. These two factors are the main reasons for students' negative attitudes towards entrepreneurship. Colleges can stimulate the potential of students' self-development through the improvement of entrepreneurial psychological education courses, the construction of psychological consultation institutions on campus, and the establishment of interactive platforms for entrepreneurship. Then, students' entrepreneurial psychology can be cultivated in an all-round way. At present, the overall entrepreneurial consciousness of college students is still relatively weak. The colleges should cultivate entrepreneurial innovative talents by strengthening the psychological education of entrepreneurship for students, thereby helping college students to achieve entrepreneurial success.